2002
DOI: 10.1111/j.1151-2916.2002.tb00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Machinability of Silicon Nitride/Boron Nitride Nanocomposites

Abstract: The machinability and deformation mechanism of Si3N4/BN nanocomposites were investigated in the present work. The fracture strength of Si3N4/BN microcomposites remarkably decreased with increased hexagonal graphitic boron nitride (h‐BN) content, although machinability was somewhat improved. However, the nanocomposites fabricated using the chemical method simultaneously had high fracture strength and good machinability. Hertzian contact tests were performed to clarify the deformation behavior by mechanical shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 43 publications
3
83
1
Order By: Relevance
“…The bending strength was 400-450 MPa, which were the same level as that of the conventional monolithic alumina ceramics while the fracture toughness was 3.7-3.9 MPa·m 0.5 , which were little higher than that of the conventional monolithic alumina ceramics. The Vickers hardness was [11][12][13][14] GPa, which was the same level as that of zirconia ceramics. 9.…”
mentioning
confidence: 63%
“…The bending strength was 400-450 MPa, which were the same level as that of the conventional monolithic alumina ceramics while the fracture toughness was 3.7-3.9 MPa·m 0.5 , which were little higher than that of the conventional monolithic alumina ceramics. The Vickers hardness was [11][12][13][14] GPa, which was the same level as that of zirconia ceramics. 9.…”
mentioning
confidence: 63%
“…Thus, it is concluded that the observed high strength of SiCBN nanocomposites is attributable mainly to the reduction of the critical flaw size by the nano-sized h-BN dispersion. The mechanical properties of h-BN dispersed nanocomposites [23][24][25][32][33][34] are summarized in Table. 1. It is found that all the produced h-BN dispersed nanocomposites have the unique mechanical property of high strength though low Young's modulus.…”
Section: Microstructure Of Sicbn Nanocompositesmentioning
confidence: 99%
“…For fabrication of Al 2 O 3 /BN nanocomposites, the process presented in previous paper 12) was adopted. The starting powders for the nanocomposites were the commercially available aAl 2 O 3 powder (AKP53, Sumitomo Chemicals, Tokyo) and boric acid (Reagent grade, Wako Pure Chemi Fig.…”
Section: Experimental 21 Fabrication Of Test Specimensmentioning
confidence: 99%
“…8)11) However, by the addition of microsized hBN particles as a second phase, it has been reported that fracture strength decrease remark ably with an increase in hBN content due to the aggregation of BN particles caused by conventionally mixing commer cially powders, even though its machinability was somewhat improved. 10) Also, large grain size hBN particle maybe in itiate fracture, because Young's modulus of hBN is lower than 1/6 of that of monolithic Al 2 O 3 . Therefore, for hBN dispersed ceramic composites, the nanocomposite struc ture, which is the homogeneous dispersion of nanosized h BN particles into Al 2 O 3 matrix, is probably eective to en hance the fracture strength of machinable Al 2 O 3 /BN compo sites.…”
Section: Introductionmentioning
confidence: 99%